Uses of Online Integrated Learning in Developing Grade 9 Students’ Reading Comprehension - Pattaraporn Wongta; Autthapon Intasena; Thussaneewan Srimunta (Journal of Educational Issues, 2024)
The purposes of the study were to investigate the effectiveness of an online integrated learning management plan on grade 9 students’ reading comprehension and to study the students’ satisfaction with the online integrated learning management plan. The study was conducted in a one-group experimental design. The participants were 33 grade 9 students in a public school in Thailand. The instruments were a learning management plan designed using the integration of online learning, a reading comprehension test, and a satisfaction questionnaire. The statistics of percentage, mean score, standard deviation, a paired samples t-test, and the effectiveness index with the determining criteria of 75/75 were used to analyze the effectiveness of the treatment. The results indicate the effectiveness of learning management in a reading classroom. Moreover, the online environment also brought about a satisfying learning experience for the participants. The results contribute to the investigation of online integrated learning on reading development as they provide a piece of evidence to support the instructional method in the reading classroom with learners of a certain context.